Double-layer nanofiber patch material applied to urinary tract repair and reconstruction and preparation method of double-layer nanofiber patch material
By using a bilayer nanofiber patch material and using the combination of antimicrobial peptides and Ti3C2-MXene modified ceria nanoenzyme, the problems of insufficient biocompatibility and poor antibacterial performance of existing urethral repair materials are solved, and effective patency and safety of urethral repair are achieved.
Patent Information
- Application Number
- CN202411914314.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
Existing urethral repair materials have problems such as insufficient biocompatibility, poor antibacterial performance, as well as long-term complications and psychological damage, making it difficult to effectively solve the challenges of urethral stenosis and repair.
A double-layer nanofiber patch material was used, the first layer was polylevolactate nanofibers loaded with antimicrobial peptides, and the second layer was silk fibroin nanofibers loaded with Ti3C2-MXene modified ceria nanozyme, and prepared by electrospinning.
The biocompatibility of the material and no biotoxic side effects are achieved. The first layer has broad-spectrum antibacterial effects, and the second layer has antioxidant and anti-inflammatory effects, which can effectively promote smooth urethral repair and reduce the risk of complications.
Smart Images

Figure CN119746166A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical materials, and in particular relates to a double-layer nanofiber patch material used for urinary tract repair and reconstruction and a preparation method thereof. Background Art
[0002] Urethral diseases seriously affect the urination function and quality of life of patients, and even lead to renal failure. Therefore, the reconstruction of urethral stricture is of great significance in the field of urology. Due to the lack of ideal urethral repair grafts, the patient's own tissue is often used for urethral repair in clinical practice, such as penile scrotal pedicle flap, oral mucosa, tongue mucosa, colon mucosa, etc. However, the use of autologous tissue can cause severe trauma to the site, as well as long-term complications and psychological damage. Artificial engineering scaffolds have controllability, biodegradability and mechanical properties, and show great potential in urethral regeneration.
[0003] The pathological process after urethral injury can be divided into three periods: Injury stage: In this stage, the urethral tissue is damaged, urine leaks out and may cause bleeding at the urethral opening. Inflammatory stage: When closed urethral injury lasts for more than 72 hours or signs of infection appear within 72 hours after open urethral injury, the inflammatory stage is entered. In this stage, the tissue is swollen and there may be a risk of secondary bacterial infection. Stricture stage: If the injury lasts for more than 3 weeks, the inflammation gradually dissipates, but the local fibrous tissue proliferates actively, followed by scar formation, leading to urethral narrowing. This is the biggest challenge in the reconstruction and repair of urethral strictures. Due to the lack of elasticity of scar tissue, the normal function of the urethra is seriously affected, urination is difficult, and even completely blocked.
[0004] Nanomaterials have unique surface effects, quantum size effects, small size effects, and macroscopic quantum tunneling effects, which make them exhibit special properties different from conventional materials. Cerium dioxide (CeO2) is a common nanomaterial. At the nanoscale, due to the generation of surface oxygen defects, some Ce in cerium dioxide 3+ and Ce 4+It can be reversibly converted to stabilize defects, and the larger specific surface area provides a guarantee for excellent catalytic performance. The above properties make nano-cerium dioxide have high practical and research value in the fields of biomedicine, energy catalysis, mechanical polishing, radiation protection, environmental protection, etc. MXene is a class of two-dimensional nanomaterials composed of transition metal carbides or nitrides. This type of material has attracted much attention due to its unique layered structure, excellent electrochemical properties and good conductivity. These functional groups give MXene materials special physical and chemical properties, making them show great application potential in catalysis, energy storage, electromagnetic shielding, sensors and other fields. Ti3C2-MXene is one of the earliest discovered and widely studied MXene materials, and it has shown broad application prospects in catalysis, energy storage, composite materials and many other fields. Poly L-lactic acid (PLLA), also known as poly L-lactic acid, is a biodegradable polymer mainly obtained by condensation polymerization of L-lactic acid monomers. The degradation mechanism of PLLA is mainly hydrolysis, and the final product is non-toxic lactic acid, which makes it an ideal material for in vivo implantation. PLLA has broad application prospects in the biomedical field due to its good biocompatibility and mechanical strength, such as the manufacture of bioabsorbable sutures, tissue engineering scaffolds, drug controlled release systems, etc. Silk fibroin (SF) is a natural protein extracted from silkworm cocoons, known for its excellent mechanical properties, biocompatibility and biodegradability. Silk fibroin also has good mechanical properties and an adjustable degradation rate, which makes it an ideal choice for building artificial organs and tissue repair materials. This protein has been widely used in the biomedical field, including tissue engineering, drug delivery systems, wound dressings, etc. Antimicrobial peptides are a class of alkaline polypeptide substances with antibacterial activity. Most of these active polypeptides have the characteristics of strong alkalinity, thermal stability and broad-spectrum antibacterial. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies of existing urethra repair materials and to provide a double-layer nanofiber patch material for urinary tract repair and reconstruction and a preparation method thereof.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A double-layer nanofiber patch material used for urinary tract repair and reconstruction, wherein the first layer is poly-L-lactic acid nanofiber loaded with antimicrobial peptides, and the second layer is silk fibroin nanofiber loaded with Ti3C2-MXene modified ceria nanozyme (MCe nanozyme).
[0008] The Ti3C2-MXene modified cerium dioxide nanozyme is synthesized by a hydrothermal method using a single layer of Ti3C2-MXene, cerium nitrate and ammonia water.
[0009] Furthermore, the Ti3C2-MXene modified cerium dioxide nanozyme is prepared by a method comprising the following steps: adding a single layer of Ti3C2-MXene, cerium nitrate and ammonia water to water and fully dispersing them before conducting a hydrothermal reaction; after the reaction is completed, the suspension obtained is washed, centrifuged and dried to obtain the Ti3C2-MXene modified cerium dioxide nanozyme.
[0010] The cerium nitrate may be hexahydrated cerium nitrate, and the ammonia water is preferably 25% ammonia water. The mass ratio between the single-layer TiC3C2-MXene and the hexahydrated cerium nitrate is preferably 1:0.1-0.5; and the final concentration of the ammonia water is preferably 2.5-5%.
[0011] The dispersion is preferably achieved by ultrasound in an ice bath, and the ultrasound time is preferably 15 to 30 minutes.
[0012] The hydrothermal reaction is preferably carried out in a polytetrafluoroethylene-lined high-pressure reactor, and the volume of the reaction liquid is less than or equal to 70% of the total volume of the polytetrafluoroethylene liner.
[0013] The conditions of the hydrothermal reaction are preferably 170-200° C. for 17-20 h. Temperatures below 120° C. will reduce the yield of MCe nanozymes, and temperatures above 200° C. will create safety risks.
[0014] The washing is preferably performed by washing with deionized water and then with anhydrous ethanol; the rotation speed of the centrifugation is preferably 3000-5000 rpm.
[0015] The drying is preferably vacuum freeze drying, and the conditions of the vacuum freeze drying are preferably -30 to -50°C and 24 to 48 hours.
[0016] The preparation method of the double-layer nanofiber patch material for urinary tract repair and reconstruction is an electrospinning method, which includes the following steps: electrospinning a blended solution containing poly-L-lactic acid (PLLA) and antimicrobial peptides to obtain a first layer of nanofibers, electrospinning a blended solution containing silk fibroin (SF) and Ti3C2-MXene modified cerium dioxide nanozyme to obtain a second layer of nanofibers, and then using methanol to modify the silk fibroin nanofiber layer to transform the microstructure of the silk fibroin from an α-helix to a β-fold. After drying, disinfection and sterilization, a double-layer nanofiber patch material for urinary tract repair and reconstruction is obtained.
[0017] The solvent of the blended solution containing poly-L-lactic acid and antimicrobial peptide or the blended solution containing silk fibroin and Ti3C2-MXene modified ceria nanozyme includes hexafluoroisopropanol. In the blended solution containing poly-L-lactic acid and antimicrobial peptide, the concentration of poly-L-lactic acid is preferably 8% to 13% (w / v), and the concentration of antimicrobial peptide is preferably In the mixed solution containing silk fibroin and Ti3C2-MXene modified ceria nanozyme, the concentration of silk fibroin is preferably 8% to 13% (w / v), and the concentration of MXene modified ceria nanozyme is preferably 0.5% to 2% (w / v).
[0018] The parameters of the first layer electrospinning are preferably set to: pump speed of 1 mL / h to 1.5 mL / h, voltage of 10 kv to 15 kv, receiving spacing of 15 to 18 cm, ambient temperature of 20 to 30 ° C, air humidity of 40 to 60%, and spinning time of 24 to 48 h.
[0019] The parameters of the second layer electrospinning are preferably set to: pump speed of 1mL / h~1.5mL / h, voltage of 10kv~15kv, receiving spacing of 15~18cm, ambient temperature of 20~30℃, air humidity of 40~60%, and spinning time of 12~24h.
[0020] The drying is preferably performed by ventilation and air-drying in a fume hood, and the disinfection and sterilization is preferably performed by ultraviolet irradiation.
[0021] The application of the above-mentioned double-layer nanofiber patch material for urinary tract repair and reconstruction in the preparation of materials for urinary tract repair and reconstruction.
[0022] A urinary tract repair and reconstruction material comprises the above-mentioned double-layer nanofiber patch material used for urinary tract repair and reconstruction.
[0023] The schematic diagram of using the double-layer nanofiber patch material of the present invention as a urinary tract repair and reconstruction material for urinary tract repair and reconstruction surgery is shown in FIG. Figure 6 As shown, the first layer of nanofibers (antibacterial layer PC) is placed on the outside (urethral lumen surface), and the second layer of nanofibers (antioxidant layer SMCe) is placed on the inside (urethral tissue surface).
[0024] The present invention has the following advantages and beneficial effects:
[0025] The double-layer nanofiber patch material of the present invention is biocompatible and has no biological toxic side effects. The first layer of nanofibers has a broad-spectrum antibacterial effect, including killing Gram-positive bacteria such as Staphylococcus aureus and Gram-negative bacteria such as Escherichia coli; the second layer of nanofibers has antioxidant and anti-inflammatory effects, and can reduce excessive activity in vitro and in vivo. The double-layer nanofiber patch material of the present invention exerts antibacterial, anti-inflammatory and antioxidant functions through a double-layer structure, and can be used to repair urethral defect sites and promote urethral repair and patency.
[0026] The precursors and raw materials used in the preparation of the double-layer nanofiber patch material of the present invention are all basic reagents commonly used in laboratories, and the equipment used is basic equipment commonly used in laboratories. The preparation method is simple, the conditions are mild, the energy consumption is low, and the overall cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an electron microscope image of MXene-modified cerium dioxide nanozyme (MCe nanozyme). The size of the MCe nanozyme material is about 5μm.
[0028] Figure 2 These are the X-ray diffraction patterns (XRD) of MXene, ceria, and MCe nanozyme. The XRD characteristic peaks of MCe nanozyme have some characteristic peaks of MXene and ceria.
[0029] Figure 3 Bright field and electron microscope images of the double-layer nanofiber patch material (PC@SMCe) prepared in the present invention. The PC@SMCe nanofiber patch material is composed of two layers of different nanofibers, the first layer is made by electrospinning PLLA blended antimicrobial peptides, and the second layer is made by electrospinning SF blended MCe nanozymes.
[0030] Figure 4 The test results of PC@SMCe nanofiber patch material scavenging DPPH free radicals. PC@SMCe nanofiber patch material has the ability to scavenge DPPH·.
[0031] Figure 5 The antibacterial test results of PC@SMCe nanofiber patch material are shown in Figure 2. The PC@SMCe nanofiber patch material inhibited the proliferation of Staphylococcus aureus and Escherichia coli, indicating that it has a broad-spectrum antibacterial activity.
[0032] Figure 6 Schematic diagram of urethral defect repair surgery using PC@SMCe nanofiber patch material, with the antibacterial layer PC placed on the outside (urethral lumen surface) and the antioxidant layer SMCe placed on the inside (urethral tissue surface).
[0033] Figure 7 This is a photo of a urethral defect repair surgery using PC@SMCe nanofiber patch material.
[0034] Figure 8 This is a comparison of the X-ray urethrography before and after using the decellularized porcine small intestinal submucosal matrix patch and the PC@SMCe nanofiber patch material to repair urethral stricture. After the PC@SMCe nanofiber patch material was repaired, the rabbit's urethra was unobstructed in the fifth week after surgery. DETAILED DESCRIPTION
[0035] The following examples are used to further illustrate the present invention, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.
[0036] Example 1
[0037] (1) Preparation of MXene-modified ceria nanozymes
[0038] A single-layer Ti3C2-MXene flake was obtained by etching and intercalation. 30 mg of Ti3C2-MXene was dispersed in 30 mL of water, ultrasonicated in an ice bath, 3 mg of cerium nitrate hexahydrate was added, ultrasonicated in an ice bath, and 4 mL of 25% ammonia water was added to continue ultrasonication to obtain a mixed liquid. The mixed liquid was transferred to a polytetrafluoroethylene-lined autoclave and heated at 170 ° C in a high-temperature oven for 17 to 20 hours. After the reaction was completed, it was washed with deionized water and anhydrous ethanol in turn, and centrifuged at 3000 rpm to remove unreacted impurities. The precipitate was vacuum freeze-dried at -50 ° C to obtain Ti3C2-MXene-modified cerium dioxide nanozyme particles, named MCe nanozyme. MCe nanozyme needs to be placed in a -20 ° C environment to prevent oxidation.
[0039] The electron microscopy image of the prepared MCe nanozyme is shown in Figure 1 As shown in Figure 2, its size is about 5 μm. The X-ray diffraction patterns (XRD) of MCe nanozyme, MXene, and ceria are shown in Figure 2. Figure 2 As shown, the XRD characteristic peaks of MCe nanozyme have some characteristic peaks of MXene and ceria.
[0040] (2) Preparation of electrospinning solution
[0041] PLLA was dissolved in hexafluoroisopropanol to obtain a 10% (w / v) PLLA solution; The antimicrobial peptide CRRI3 (REERWF-NH2) was added and mixed thoroughly to obtain solution A. Silk fibroin (SF) was dissolved in hexafluoroisopropanol to obtain a 10% (w / v) SF solution, and 1% (w / v) MCe nanozyme was added to the 10% SF solution and mixed thoroughly to obtain solution B.
[0042] (3) Preparation of double-layer nanofiber patch material using electrospinning equipment
[0043] Solution A was first used for the first layer of electrospinning. The parameters of the first layer of electrospinning nanofibers were set as follows: pump speed of 1 mL / h, voltage of 13 kv, receiving spacing of 18 cm, ambient temperature of 30 °C, air humidity of 40%, and spinning time of 24 h. Immediately after the first layer of spinning, the second layer of solution B was electrospinned. The parameters of the second layer of electrospinning nanofibers were set as follows: pump speed of 1 mL / h, voltage of 13 kv, receiving spacing of 18 cm, ambient temperature of 30 °C, air humidity of 40%, and spinning time of 24 h. The second layer of nanofibers was modified with methanol to transform the microstructure of silk fibroin from α helix to β folding. The nanofiber patch obtained by electrospinning was placed in a fume hood for ventilation and drying for 24 hours, and sterilized by ultraviolet irradiation to obtain a sterile double-layer nanofiber patch material that can be used for urinary tract repair and reconstruction. It is a white sheet patch material named PC@SMCe nanofiber patch material. PC@SMCe nanofiber patch material needs to be stored in a 4 °C environment to prevent oxidation.
[0044] Bright field and electron microscopy images of the prepared PC@SMCe nanofiber patch material are shown in Figure 3 shown.
[0045] Example 2
[0046] 1,1-Diphenyl-2-picrylhydrazyl (DPPH) is a stable free radical. DPPH was used to detect the free radical scavenging ability of PC@SMCe nanofiber patch. 1 mg DPPH was weighed and dissolved in 10 mL of anhydrous ethanol. The DPPH solution was divided into centrifuge tubes, 5 mL per group, and 1 cm 2 The PC@SMCe nanofiber patch was added and set as the PC@SMCe group; the other group was not added and set as the blank control group. The centrifuge tube was placed in a 37°C constant temperature shaker and incubated in the dark at a speed of 120 rpm. After 24 hours, centrifuge at 3000 rpm for 5 minutes, take 1 mL of the supernatant, and use a UV spectrophotometer to measure the absorbance value of the supernatant at a wavelength of 350nm to 800nm. The measured DPPH absorbance curves of the PC@SMCe nanofiber patch and the blank control group are shown in the figure. Figure 4 As shown, the results demonstrated that PC@SMCe nanofiber patch could effectively scavenge DPPH free radicals.
[0047] Example 3
[0048] The antibacterial effect of PC@SMCe nanofiber patch was tested by bacterial plate cloning experiment. Single colonies of Escherichia coli and Staphylococcus aureus were picked from the bacterial culture dish with a sterile pipette tip, placed in 10mL liquid LB, and cultured in a constant temperature shaker with the temperature set at 37°C and the speed at 180 rpm for 1 hour. Then, 1cm 2 PC@SMCe nanofiber patch was placed on the plate and cultured for 3 to 6 hours. 100 μL of the cultured bacterial liquid was dropped into a solid LB culture dish and the liquid was spread evenly using a glass rod. The culture dish was placed in a 37°C constant temperature incubator and cultured upside down for 24 hours, and then the colony status of the culture dish was recorded.
[0049] The image of the colony in the culture dish is as follows Figure 5 As shown, compared with the blank control group, the number of colonies in the PC@MCe nanofiber patch group was smaller. The results showed that the PC@MCe nanofiber patch could significantly inhibit the proliferation of Escherichia coli and Staphylococcus aureus.
[0050] Example 4
[0051] Schematic diagram of urethral defect repair surgery using PC@MCe nanofiber patch Figure 6 As shown, the antibacterial layer PC is placed on the outside (urethra lumen surface), and the antioxidant layer SMCe is placed on the inside (urethra tissue surface).
[0052] Animal experiments were conducted using New Zealand white rabbits to verify that the PC@MCe nanofiber patch can repair urethral stricture.
[0053] A 0.5 cm × 0.3 cm defect was created in the urethra of a New Zealand white rabbit by surgery. A decellularized porcine small intestinal submucosal matrix patch (purchased from Cook Biotech, USA, specification model C-SLH-4S-7X10) or a PC@MCe double-layer nanofiber patch was sutured to the defect area to cover the gap. The first layer of nanofibers was placed on the urethral lumen surface, and the second layer of nanofibers was placed on the urethral tissue surface. Figure 7 As shown. Ten weeks after surgery, X-ray urethrography was performed on the blank control group, the decellularized porcine small intestinal submucosal matrix patch, and the PC@SMCe double-layer nanofiber patch material. The results of X-ray urethrography are shown in Figure 8 As shown, the width of the narrowest part of the urethra in the blank control group was 16.09±3.64mm; the width of the narrowest part after repair with the decellularized porcine small intestinal submucosal matrix patch was 44.15±1.10mm; after the urethra was repaired with the PC@SMCe nanofiber patch, the width of the narrowest part of the rabbit urethra was 86.58±0.96mm. The repair effect of the PC@SMCe nanofiber patch on the urethra was 2.51 times that of the decellularized porcine small intestinal submucosal matrix patch.
[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A double-layer nanofiber patch material for urinary tract repair and reconstruction, characterized in that: The first layer of the material is poly-L-lactic acid nanofibers loaded with antimicrobial peptides, and the second layer is silk fibroin nanofibers loaded with Ti3C2-MXene modified ceria nanozyme.
2. The double-layer nanofiber patch material according to claim 1, characterized in that: The Ti3C2-MXene modified cerium dioxide nanozyme is synthesized by a hydrothermal method using a single layer of Ti3C2-MXene, cerium nitrate and ammonia water.
3. The double-layer nanofiber patch material according to claim 1, characterized in that: The Ti3C2-MXene modified cerium dioxide nanozyme is prepared by a method comprising the following steps: adding a single layer of Ti3C2-MXene, cerium nitrate and ammonia water to water and fully dispersing them before conducting a hydrothermal reaction; after the reaction is completed, washing, centrifuging and drying are performed to obtain the Ti3C2-MXene modified cerium dioxide nanozyme.
4. The double-layer nanofiber patch material according to claim 2 or 3, characterized in that: The cerium nitrate is hexahydrated cerium nitrate, and the ammonia water is 25% ammonia water; the mass ratio between the single-layer TiC3C2-MXene and the hexahydrated cerium nitrate is preferably: 1:0.1-0.5; the final concentration of the ammonia water is preferably 2.5-5%.
5. The method for preparing the double-layer nanofiber patch material according to any one of claims 1 to 4, characterized in that: The preparation method is an electrostatic spinning method.
6. The method for preparing the double-layer nanofiber patch material according to claim 5, characterized in that: The method comprises the following steps: electrospinning a mixed solution containing poly-L-lactic acid and antimicrobial peptide to obtain a first layer of nanofibers; electrospinning a mixed solution containing silk protein Ti3C2-MXene modified cerium dioxide nanozyme to obtain a second layer of nanofibers; and modifying the second layer of nanofibers with methanol. After drying, disinfection and sterilization, the double-layer nanofiber patch material is obtained.
7. The method for preparing the double-layer nanofiber patch material according to claim 6, characterized in that: In the blended liquid containing poly-L-lactic acid and antimicrobial peptide, the concentration of poly-L-lactic acid is 8% to 13%, and the concentration of antimicrobial peptide is In the mixed solution containing silk fibroin and Ti3C2-MXene modified cerium dioxide nanozyme, the concentration of silk fibroin is 8% to 13%, and the concentration of MXene modified cerium dioxide nanozyme is 0.5% to 2%.
8. Use of the double-layer nanofiber patch material according to any one of claims 1 to 4 in preparing materials for urinary tract repair and reconstruction.
9. A urinary tract repair and reconstruction material, characterized in that: A double-layer nanofiber patch material comprising any one of claims 1 to 4.
10. The urinary tract repair and reconstruction material according to claim 9, characterized in that: When the double-layer nanofiber patch material is used in urinary tract repair and reconstruction surgery, the first layer of nanofibers is placed on the outside, and the second layer of nanofibers is placed on the inside.